Thermal Transformation of Indigenous Diaspore - Muhammad Ashraf Kamal; Syed Mumtaz Danish Naqvi; Syed Mohib Raza Kazmi; Kashif Riaz; Shaikh Mohiuddin (Journal of Basic & Applied Sciences, 2015)
Indigenous diaspore is a high density hard mineral. It becomes harder on heating up to 550oC. The dispore has been characterized thermally by thermal gravimetric analysis and x-ray diffraction. Results show that the indigenous mineral increases its density after heating at various temperatures for 1 hour. Increase in density points out the increase in hardness due to the formation of a more crystalline compact material corundum using as abrasive.